The dynamics of social assistance benefit receipt in Germany: State dependence before and after the 'Hartz reforms' - Sebastian Königs (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
In this article, we study state dependence in social assistance receipt in Germany using annual survey data from the German Socio-Economic Panel (SOEP) for the years 1995-2011. We show that there is considerable observed state dependence, with an average persistence rate in benefits of 68% compared to an average entry rate of below 4%. To identify a possible structural component in state dependence, we estimate a series of dynamic random-effects probit models that control for unobserved heterogeneity and endogeneity of initial condition. We find evidence of substantial state dependence in benefit receipt. Our estimates suggest that benefit receipt one year ago raises the likelihood of benefit receipt today by a factor of 3.7. This corresponds to an average partial effect of over 14 percentage points. Average predicted entry and persistence rates are much higher in Eastern Germany than in Western Germany, absolute levels of structural state dependence however are comparable. We do not find evidence for much time variation in state dependence. This holds true also for the time around the Hartz reforms.
Keywords: I38; J60; J64; C23; 330; social assistance; welfare benefits; state dependence; Hartz reforms